Maturidade digital em um órgão público: um estudo no departamento estadual de trânsito do Espírito Santo - Simões, Wesley Rangel (2025)
From a perspective focused in the public sector, under the lens of emerging digital maturity and its diagnosis, a convergence supported by new concepts being incorporated into public administration was identified framed within a context of public and digital governance. This convergence underpins the empirical study of measuring the digital maturity of a public agency. Accordingly, this dissertation aimed to examine the digital maturity at Detran-ES, its outcomes, and possible challenges, based on the adapted application of the World Bank's GovTech model. This applied research employed mixed methods with a convergent approach, combining quantitative analysis of secondary data and qualitative analysis of institutional public documents. The GovTech model was adapted to the context of a state autarchy, considering its specific role in the traffic sector. The quantitative analysis indicated that Detran-ES achieved a Very High digital maturity classification, with a GovTech Maturity Index (GTMI) score of 80.76%, demonstrating significant investments in technological infrastructure and digital governance. The qualitative analysis, based on 44 questions and multiple documentary sources, revealed, on the other hand, possibility for improvement in dimensions such as the provision of digital services to citizens and digital social engagement. The results suggest that, despite internal technological advancement, there is still a need to expand practices focused on citizen-centeredness and social participation. This research contributes to the field of Public Administration by proposing a practical and replicable assessment of digital maturity in public agencies, highlighting the importance of balancing technological infrastructure, organizational transformation, and the democratization of digital services